Doubling farmers’ income by 2022: pathway and strategies for wheat producers - Singh, G. P.; R., Sendhil; Kumar, Anuj; Singh, Satyavir; Tripathi, S. C. (Indian Farming, 2018)
The ambition of the Government of India has to be met coherently through productivity enhancement coupled with cost reduction, price realization and policy support. Income from a single crop or commodity will not fulfil the target of doubling farmers’ income but it has to emulate from farm and nonfarm sources. Diversification of activities which yields better remuneration (region specific) should be the ideal strategy. Clearly, in the case of wheat, the whole value chain has to be strengthened to be on the track of doubling the income for all classes of farmers.